Development of a DNA Vaccine for Melanoma Metastasis by Inhalation Based on an Analysis of Transgene Expression Characteristics of Naked pDNA and a Ternary Complex in Mouse Lung Tissues - Yukinobu Kodama; Mikiro Nakashima; Tadayuki Nagahara; Natsuko Oyama; Junya Hashizume; Hiroo Nakagawa; Hitomi Harasawa; Takahiro Muro; Tomoaki Kurosaki; Chikamasa Yamashita; Mitsuru Hashida; Takashi Kitahara; et al. (MDPI AG, 2020)
The present study investigated a pulmonary delivery system of plasmid DNA (pDNA) and its application to melanoma DNA vaccines. pCMV-Luc, pEGFP-C1, and pZsGreen were used as a model pDNA to evaluate transfection efficacy after inhalation in mice. Naked pDNA and a ternary complex, consisting of pDNA, dendrigraft poly-l-lysine (DGL), and γ-polyglutamic acid (γ-PGA), both showed strong gene expression in the lungs after inhalation. The transgene expression was detected in alveolar macrophage-rich sites by observation using multi-color deep imaging. On the basis of these results, we used pUb-M, which expresses melanoma-related antigens (ubiquitinated murine melanoma gp100 and tyrosinase-related protein 2 (TRP2) peptide epitopes), as DNA vaccine for melanoma. The inhalation of naked pUb-M and its ternary complex significantly inhibited the metastasis of B16-F10 cells, a melanoma cell line, in mice. The levels of the inflammatory cytokines, such as TNF-α, IFN-γ, and IL-6, which enhance Th1 responses, were higher with the pUb-M ternary complex than with naked pUb-M and pEGFP-C1 ternary complex as control. In conclusion, we clarified that the inhalation of naked pDNA as well as its ternary complex are a useful technique for cancer vaccination.